2005
DOI: 10.1254/jphs.fpj04058x
|View full text |Cite
|
Sign up to set email alerts
|

SKI306X Suppresses Cartilage Destruction and Inhibits the Production of Matrix Metalloproteinase in Rabbit Joint Cartilage Explant Culture

Abstract: Abstract. SKI306X was previously found to have cartilage protective effects in the experimental osteoarthritis (OA) model. To investigate the chondro-protective benefits of SKI306X for its capacity in altering changes in cartilage metabolism and molecular mechanisms of cartilage protective action, SKI306X is studied in rabbit cartilage explants culture. To investigate the protective effect of SKI306X on cartilage catabolism, we assessed collagen degradation in rabbit cartilage explants treated with interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
1
21
1
Order By: Relevance
“…Dual deletion of ADAMTS-4 and ADAMTS-5 in mice resulted in significant protection against proteoglycan degradation, which was comparable with that observed with deletion of ADAMTS-5 alone, and decreased the severity of murine OA (40). Recent studies show that collagen and proteoglycan release from cartilage can indeed be prevented by treatment with an inhibitor of MMP transcription (41,42). It has been also reported that increased levels of MMP-3 are co-localized with cell death and broken cartilage (proteoglycan and collagen) in models of OA (43 -45).…”
Section: Discussionsupporting
confidence: 58%
“…Dual deletion of ADAMTS-4 and ADAMTS-5 in mice resulted in significant protection against proteoglycan degradation, which was comparable with that observed with deletion of ADAMTS-5 alone, and decreased the severity of murine OA (40). Recent studies show that collagen and proteoglycan release from cartilage can indeed be prevented by treatment with an inhibitor of MMP transcription (41,42). It has been also reported that increased levels of MMP-3 are co-localized with cell death and broken cartilage (proteoglycan and collagen) in models of OA (43 -45).…”
Section: Discussionsupporting
confidence: 58%
“…Recently, a great variety of herbal remedies have been proposed for OA therapy, such as Capparis spinosa extracts (Panico et al 2005), green tea polyphenols (Ahmed et al 2004), genistein (Hooshmand et al 2007), resveratrol (Csaki et al 2008), curcumin (Shakibaei et al 2007), etc. Many plants from Clematis species have been demonstrated to possess anti-inflammatory and chondro-protective effects (Choi et al 2002;Kim et al 2005a;Kim et al 2005b; Lee et al 2005;Li et al 2006;Park et al 2006). Among them, Clematis chinensis Osbeck (Ranunculaceae), which is mainly distributed in southern China and contains several triterpenoid saponins (Mimaki et al 2004), has long been used in traditional Chinese medicine to treat joint diseases including OA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, down-regulation of aggrecanases, MMPs and up-regulation of TIMPs would be reasonable therapeutic targets for the treatment of OA. Recently report, proteoglycan release from cartilage can prevent by treatment with inhibitor of MMP transcription (Ishikawa et al, 2005;Kim et al, 2005). Recent research demonstrated that MMP-1 was involved in OA development in rabbit ACLT model and the amount of its expression was related with the degree of cartilage degradation .…”
Section: Discussionmentioning
confidence: 99%